2020
DOI: 10.1111/sum.12655
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic and inorganic carbon sequestration by consecutive biochar application: Results from a decade field experiment

Abstract: Biochar addition can expand soil organic carbon (SOC) stock and has potential ability in mitigating climate change. Also, some incubation experiments have shown that biochar can increase soil inorganic carbon (SIC) contents. However, there is no direct evidence for this from the field experiment. In order to make up the sparseness of available data resulting from the long‐term effect of biochar amendment on soil carbon fractions, here we detected the contents and stocks of the bulk SIC and SOC fractions based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…wheat, corn and ryegrass) reported a significant increase in soil C as a result of biochar application (Shi et al 2021;Weng et al 2017). Shi et al (2021) observed 16 to 82% increase in soil organic C content by 10 years annual application of 4.5 and 9.0 Mg ha -1 corn cobs biochar in winter wheat-corn rotation in a silt loam soil in Shandong Province, China. In their study biochar C was mainly allocated to particulate organic C fraction (38-166%).…”
Section: Soil C and N Contentmentioning
confidence: 99%
“…wheat, corn and ryegrass) reported a significant increase in soil C as a result of biochar application (Shi et al 2021;Weng et al 2017). Shi et al (2021) observed 16 to 82% increase in soil organic C content by 10 years annual application of 4.5 and 9.0 Mg ha -1 corn cobs biochar in winter wheat-corn rotation in a silt loam soil in Shandong Province, China. In their study biochar C was mainly allocated to particulate organic C fraction (38-166%).…”
Section: Soil C and N Contentmentioning
confidence: 99%
“…A field experiment conducted over a period of a decade found that biochar application significantly increased both inorganic and organic carbon contents in soil, with the most significant increase in the particulate organic carbon content. However, biochar application was also found to have reduced silt and clay associated organic carbon, likely due to biochar's priming effect on natural soil carbon (Shi et al., 2021). The application of soil amendment may also enhance aggregate formation and improve the stability of soil organic matter, for example a structural equation model revealed that manure fertilization stimulates microbial growth, which renders polysaccharide‐C and aliphatic‐C in intra‐particulate organic matter to facilitate macro‐aggregate formation (Wen et al., 2021).…”
Section: Soil Carbon Sequestrationmentioning
confidence: 99%
“…In addition, there is vast potential for the sequestration of soil inorganic carbon as secondary carbonates and bi‐carbonates (Lal, 2019). For instance, a recent study showed that although biochar addition can expand soil organic carbon stocks, it can also increase the dissolved inorganic carbon content in soils (Shi et al, 2020).…”
Section: –2020: the Contributions Of Soil Science To Five Grand Chall...mentioning
confidence: 99%